PENGHITUNGAN, PENYETORAN, PELAPORAN PPN DAN MEKANISME PENGISIAN E-FAKTUR PADA PT BUKIT ANGKASA MAKMUR - Dewi Aprida; Putri Juniasih (JURNAL LENTERA AKUNTANSI, 2022)
The tax sector is a very important revenue source in development financing. One of the efforts made to increase revenue comes from Value Added Tax. Value Added Tax is imposed on the value of goods or services in circulation from producers to consumers, in English it is called Value Added Tax (VAT). The purpose of preparing this final assignment is to find out the calculation, deposit, reporting of VAT and the mechanism for filling in e-invoices at PT Bukit Angkasa Makmur. Collecting this data with descriptive research, namely by collecting the required data so that the writer can analyze and draw conclusions from the data collected. The results of the study show that PT Bukit Angkasa Makmur calculates the VAT rate of 10% which is linked to the Tax Imposition Basis (DPP) in accordance with the Value Added Tax Law. The results of the August 2021 VAT calculation show that the output tax is greater than the input tax so that underpayment and underpayment of VAT will be paid for the next period. PT Bukit Angkasa Makmur as the issuer of the Tax Invoice, when issuing the Output Tax Invoice PT Bukit Angkasa Makmur fills in the E-invoice and makes Periodic VAT SPT using the E-invoice. Deposits were made on September 18, 2021, and reporting was made at the end of the month, namely September 30, 2021. Key words: E-Invoice Calculation Mechanism